Preparation of CMC-MF/FeO(OH) by growing ferric nanoparticles on melamine foam in-situ for effective phosphate removal - Tao, Ruidong; Liu, Zihan; Li, Hao; Zheng, Mingming; Zhang, Shunxi; Qu, Mengjie; Mei, Yunjun (Journal of water process engineering, 2024)
Nanocomposite adsorbents composed of a bulk matrix and metal nanoparticles have garnered significant attention for phosphorus (P) removal. However, many nanocomposite adsorbents have been synthesized in harsh environments involving high temperature or high energy consumption, which do not meet industrial requirements; on the other hand, lots of adsorbents are synthesized by directly depositing metal hydroxides on bulk matrixs, leading to the active components shedding from the matrix due to the lack of chemical anchoring sites to immobilize metal oxide. To overcome the limitations of the existing methods, we synthesized a nanocomposite adsorbent named CMC-MF/FeO(OH) using a facile method in a mild environment. It involved coating an anchoring film prepared with carboxymethyl cellulose sodium (CMCNa) on melamine foam (MF) for in-situ growth of ferric nanoparticles. Our results demonstrated that the CMC-MF/FeO(OH) adsorbent showed promising efficiency in phosphate removal. The adsorption process was effectively described by Elovich kinetic model and Freundlich isotherm model. The adsorption mechanism was ascribed to the chemisorption by inner-sphere complex along with physical adsorption. A maximum adsorption capacity of 31.579 mg P/g which calculated by Langmuir isotherm model was achieved at 45 °C and natural pH condition in experimental range. The adsorbent exhibited effective P adsorption even in harsh environments, with the process being spontaneous and exothermic. In column applications, the CMC-MF/FeO(OH) adsorbent reduce the P content of wastewater from 4 mg P/L to 0.5 mg P/L within a short empty bed contact time of 190.95 s. Furthermore, the adsorption capacity reached 8.87 mg P/g in a column study, and trace P levels in lake water decreased to undetectable levels in a lake experiment, effectively inhibiting algae growth. •High efficient adsorbent CMC-MF/FeO (OH) for phosphorous removal was synthesized.•CMC-MF/FeO(OH) inhibited the ferric nanoparticles shed from bulk MF.•CMC-MF/FeO(OH) could treat low phosphorous containing wastewater.•Algae growth was inhibited in lake water after being treated with CMC-MF/FeO(OH).